Tumor deposits are associated with a higher risk of peritoneal disease in non‐metastatic colorectal cancer patients. Issue 6 (15th February 2023) - Khan, Hamza; Radomski, Shannon N.; Siddiqi, Amn; Zhou, Nancy; Paneitz, Dane C.; Johnston, Fabian M.; Greer, Jonathan B.
Abstract: Background and Objectives: Tumor deposit (TD) is a poor prognostic factor in colorectal cancer (CRC) patients. This study aimed to determine whether TD carry the same risk of peritoneal recurrence as known high‐risk (HR) features in CRC patients. Methods: A retrospective cohort‐study of stage I−III CRC patients from 2010 to 2015 was conducted. TD group was defined by the presence of TD on histopathology whereas HR group was defined by the presence of obstruction, perforation, or T4‐stage. Results: A total of 151 patients with CRC were identified, of which 50 had TD and 101 had a HR feature. The overall risk of peritoneal recurrence was higher in the TD group versus HR group (36.0% vs. 19.8%, p  = 0.03). The risk of peritoneum as the site of first recurrence was also higher in the TD group (22.0% vs. 12.9%, p  = 0.03). Overall cancer recurrence at any site was also higher in the TD group (56.0% vs. 34.7%, p  = 0.01). Median time to first recurrence was 1.2 (0.7−1.9) years in the TD group compared to 1.4 (0.8−2.1) years in the HR group ( p  = 0.31). Conclusions: In non‐metastatic CRC patients, TD might have a higher risk of tumor recurrence versus their HR counterparts. Alternative strategies for surveillance and treatment should be considered.